A COMPREHENSIVE REVIEW ON ADULTERATION OF RAW MATERIALS USED IN ASU DRUG MANUFACTURING (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda is a system of Indian traditional form of alternative medicine. In 20th and 21th century due to side effects of synthetic drugs, there is an increasing interesting ASU medicine. At present the adulteration of the herbal drugs is the burning problem in ASU herbal industry and it has caused a major problem in the research on commercial natural products. The deforestation and extinction of many species and incorrect identification of many plants has resulted in adulteration and substitution of raw drugs. The future development of analysis of herbs is largely depended upon reliable methodologies for correct identification, standardization and quality assurance of Ayurvedic drugs. In India normally the contamination/adulteration in food/crude drugs is done either for financial gain or due to carelessness and lack in proper hygienic condition of processing, storing, transportation and marketing. Medicinal plants constitute an effective source of traditional and modern medicine. Adulteration is considered as an intentional addition of foreign substances to increase the weight of the product or to decrease its cost. It may be due to- Confusion in vernacular names, Lack of knowledge about authentic plants, Non availability, Similarity in morphology, activity, aroma, Careless collection and other unknown reasons. This article throws a light on adulteration, types, common market adulterants in ASU medicines and prescribed Prevention methods.